DERADICALIZATION BASED ON SPIRITUAL NEUROSCIENCE THROUGH ISLAMIC EDUCATION - Listiana, Heni (Islamuna: Jurnal Studi Islam, 2021)
The development of Islamic Education course materials and deradicalization in learning is one of the efforts to prevent radicalism. Spiritual neuroscience can be used as a tool to study Islamic educational materials and deradicalization. Learning requires neuroscience to know the framework of student’s brain. This article discusses three things: (a) course material related to Islamic education and deradicalization; (b) the abstracted materials from a spiritual neuroscience perspective, and (c) models of Islamic educational material development and deradicalization in spiritual neuroscience. This article shows there are four materials related to Islamic education and deradicalization, they are: the reorientation of the meaning of jihâd, Islâm rahmah li al-‘âlamîn, multicultural values, and the strengthening of the material on love of the mother land. After being analyzed using neurospiritual operators, all such material closely relates to the meaning of life and positive emotions. Thus, Islamic education learning and deradicalization should be able to foster the formation of life meaning and positive emotions in students. [Pengembangan materi Pendidikan Agama Islam (PAI) dan deradikalasi dalam pembelajaran merupakan salah satu upaya tindakan pencegahan tindakan radikalisme. Neurosains spiritual dapat dijadikan sebagai alat untuk menelaah materi-materi Pendidikan Agama Islam (PAI) dan deradikalisasi. Pembelajaran membutuhkan neurosains untuk mengetahui kerangkan kerja otak siswa. Artikel ini membahas tiga hal: (a) materi yang berkaitan dengan Pendidikan Agama Islam (PAI) dan deradikalisasi; (b) materi-materi yang tersarikan akan dikaji dalam perspektif neurosains spiritual; dan (c) model pengembangan materi Pendidikan Agama Islam (PAI) dan deradikalisasi dalam neurosains spiritual. Artikel ini menunjukkan ada empat materi yang berkaitan dengan Pendidikan Agama Islam (PAI) dan deradikalisasi yaitu reorientasi makna jihad, Islâm rahmah li al-‘âlamîn, nilai-nilai multikultural, dan penguatan materi cinta tanah air. Setelah dianalisis dengan menggunakan operator neurospiritual semua materi tersebut berkaitan erat dengan makna hidup dan emosi positif. Dengan demikian pembelajaran Pendidikan Agama Islam (PAI) dan deradikalisasi harus mampu menumbuhkan terbentuknya makna hidup dan emosi positif pada diri siswa]